Efektivitas Penggunaan Video Pembelajaran Terhadap Hasil Belajar Pendidikan Agama Kristen Siswa SD 173304 Lumban Holbung Kabupaten Tapanuli Utara Tahun Ajaran 2023/2024 - Yuni Sihombing; Lince Sihombing; Iwan Setiawan Tarigan; Betty A. S Pakpahan; Maria Widiastuti (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The aim of this research is to determine the effectiveness of using learning videos on PAK learning outcomes for class V students at SD 173304 Lumban Holbung for the 2023/2024 academic year. The method used in this research is a quantitative method, by looking at the results of the Pre-Test and Post-Test learning. The population in this study was all class V students at SD 173304 Lumban Holbung for the 2023/2024 academic year, totaling 30 people and a sample of 30 people was determined using non-probability sampling technique with saturated sampling type. Data collected for Variable Y were 15 pre-test and post-test questions. The research results show that the use of video as a learning media is effective on learning outcomes, as evidenced by the results of the post test with an average score of 81.2 which is much better than the pre test with an average score of 59.9 previously.